CASE REPORTImprovement of the pulmonary function following percutaneous transluminal mitral commissuerotomy in a 39-year-old man exposed to sulfur mustard - Saleh, Davood Kazemi; Faizi, Fakhraddin; Saadat, Ali Reza (Archives of Medical Science, 2005)
Mustard gas causes damage to the skin, eyes, respiratory system, and gastrointestinal tract. Victims of sulfur mustard (SM) gas exposure experience different types of chronic pulmonary disease. In a case with severe MS, the complications are getting worse. Balloon dilatation is effective in providing sustained haemodynamic and symptomatic improvement of patients with severe mitral stenosis. Percutaneous Trans Luminal Mitral Commissuerotomy (PTMC) procedure performed in a 39-year-old man with coexisting mitral stenosis (MS) and idiopathic thrombocytopenic purpura (ITP) whose platelet count was 35.8x103/mm3 on admission. He was also a case known as chemical weapons victim of the Iran-Iraq war (1979-1988). He was managed with Duretics (Furosemide 20 Mg/TID/IV at first day and 40 MG/BID/Oral), Metoral 12.5Mg/BID. He was also treated with immunoglobulin G (IgG) (0.5 g/kg/d) for 4 days, resulting in a platelet count rise to 151x103/mm3. He subsequently underwent a PTMC procedure with mitral valve area (MVA) about 0.9 cm2 without a requirement of Heparin infusion. Echocardiography showed MVA rose to 2.5 cm2 and the spirometric study revealed an improvement in the pulmonary function test.